MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMK PADA SISTEM PERSAMAAN DAN PERTIDAKSAMAAN LINEAR DUA VARIABEL DENGAN PENDEKATAN PROBLEM BASED LEARNING - Yuniar Damiyanti; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study aims to: 1) find out whether the Problem Based Learning approach can improve problem solving skills in students of class X PM 1 at SMK Sangkuriang 1 Cimahi. 2) knowing whether the Problem Based Learning approach can improve student learning outcomes. The class chosen in the study was the class X PM 1 of SMK Sangkuriang 1 Cimahi. The class has low achievement and the learning response is slow. The method used is Classroom action Research through 4 phases of planning, action, observation, reflection. Data retrieval uses problem solving ability tests and student activity sheets. The research results in the percentage of students' ability to solve problems increased from 48.9%, 50%, to 61.1% for the first question. While the second question, from 60%, 61.1% to 64.4%. To complete the classical there is an increase from 36.7%, 63.3%, to 73.3%. The results of the assessment of questioning observation increased starting from 56.7%, 63.3% to 75.7%, collaboration assessments ranging from 58.3%, 65.0% to 71.7%, while independence in working on questions from cycle 1 reached 80.0%, for cycle 2 it reached 100%. Referring to the results of the study, the researchers concluded that the Problem Based Learning approach can improve problem solving skills and learning outcomes in the material system of equations and linear inequalities two variables of class X PM 1 SMK Sangkuriang 1 Cimahi academic year 2018/2019